The Effect of Systematic and Fundamental Factors on The Valuation of Cement Manufacturers in Indonesia - Wedagama, Dewa Nyoman Wiryasantika; Hakim , Dedi Budiman; Juanda, Bambang; Andati, Trias (School of Business, Bogor Agricultural University (SB-IPB), 2022)
There are two kinds of factors that influenced companies’ valuation: systematic factors and fundamental factors. The relationship between the company valuation of cement companies listed on the Indonesia Stock Exchange (IDX) and several systematic factors and fundamental factors need to be identified to know determinant factors of the valuation. The valuation of each company from 2013 to 2019 was examined to four systematic factors: the excess capacity of each company (idle capacity), market share, government infrastructure spending, and excess supply of cement in the market. As a result of the panel data regression between valuation as the dependent variable and the four systematic factors in this research, the market share has a greater influence on the valuation than the other three factors, the government infrastructure spending, the excess capacity of each company, and the oversupply of cement in the market. Fundamental factors as valuation determinants have been examined and identified, then through relative valuation-multiples, the panel data regression of valuation as the dependent variable and fundamental factors showed companies fundamental factors have a higher influence on the valuation of SMCB, SMGR and INTP, meanwhile, non-fundamental factors have a higher influence on SMCB and SMCB and SMBR valuation. Keywords: valuation, infrastructure budget, oversupply of cement market, company’s excess capacity